Volt-X electric motorcycle / Muhamad Firdaus Muhamad Izhar - Muhamad Izhar, Muhamad Firdaus (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
"Vol-X Electric Motorcycle" is a combination of artificial intelligence (AI) technology impacting motorcycle vehicles for motorcyclists. This study changes the perspective and can address issues such as near-accidents due to blind spots while riding a motorcycle. This motorcycle was also created with the aim of providing insightful information to stakeholders in the automotive industry and determining how this AI technology works to improve efficiency and safety for motorcyclists. "Vol-X Electric Motorcycle" is inspired by the design of the Honda X-ADV which is aerodynamic and comfortable. The design of this motorcycle is geometrical to look more aggressive and follow current design trends..